Developing Spiritually Grounded Lecturers through Supportive Higher Education Environments = Die ontwikkeling van geestelik gegronde dosente deur middel van ondersteunende hoëronderwysomgewings - Botha, Marga (Koers, 2026)
Integrating faith and learning in higher education presents significant challenges for lecturers. This task often involves integrating secular content with biblical principles, creating tension when attempting to deliver content from a Christian perspective. As a result, many Christian lecturers opt to present material pedagogically without critically evaluating it through a Christian worldview. Consequently, Christian higher education institutions may lack a coherent framework aligned with the Great Commission outlined in Matthew 28:19-20. Christian higher education institutions can support lecturers in integrating faith and learning within their subject content. This study employs a qualitative research design to conduct a thematic analysis of documents on the integration of faith and learning. The study revealed that faith integration in Christian higher education institutions is most effective when institutionally scaffolded and spiritually embodied. Key institutional support structures such as reformed biblical frameworks, reflective practice, academic staff, academic staff development, and communal accountability enable lecturers to align their academic teaching with the transformative mission of the Great Commission." Therefore, this article argues that Christian higher education institutions should provide institutional support to lecturers through clear policies, dedicated resources, and targeted training. Such support can help reduce tensions and foster greater coherence in educational approaches. Moreover, when teaching is aligned with the Great Commission, a holistic environment is created, which leads to a supportive community of lecturers who can share practices and strategies for effective faith integration. This research highlights the role of institutional support in overcoming the challenges of faith integration in Christian higher education. It also provides a framework for faith-learning integration, which Christian higher education institutions can explore to equip their lecturers better to fulfil their educational purpose while staying true to biblical foundations.